Ultrasound-guided percutaneous microwave ablation assisted by athree-dimensional visualization treatment platform combined with transcatheter arterial chemoembolization for a single large hepatocellular carcinoma 5 cm or larger: a preliminary clinical application. (1st January 2019) - Ren, He; An, Chao; Liang, Ping; Yu, Jie; Cheng, Zhigang; Han, Zhiyu; Liu, Fangyi; Dong, Linan; Li, Dongrui
Abstract: Objective: To assess the clinical efficiency and feasibility of ultrasound-guided percutaneous microwave ablation (US-PMWA) assisted by a three-dimensional (3D) visualization platform for treating a single large hepatocellular carcinoma (HCC) (diameter ≥5 cm). Methods: We included 40 patients with a single large HCC from May 2015 to August 2017. Nineteen patients who underwent US-PMWA assisted by a 3D visualization platform formed the 3D group; 21 patients without 3D visualization assistance formed the control group. Preoperative planning and post-procedural evaluation were performed successfully with the 3D visualization treatment platform. Thermal ablative parameters, survival and recurrence were compared between groups. Results: The primary efficacy rate and recurrence-free survival (RFS) rate in the 3D group were higher than those in the control group ( p  = .007 and p  = .014, respectively). The number of inserted probes in the 3D group was higher than that in the control group ( p  = .016). The overall survival (OS) rate in the 3D group was comparable to that of controls ( p  = .745). Estimated 3-year OS and RFS rates were 38.5% and 64.6% in the 3D group and 34.4% and 18.8% in the control group, respectively. Treatment effects were evaluated using a tumor map and confirmed by traditional contrast-enhanced ultrasound in the 3D group. After the first treatment, nine patients (47.4%) achieved complete ablation with a 5-mm safety margin. No major complications related to ablation occurred. Conclusions: US-PMWA assisted by a 3D visualization treatment platform can improve treatment efficiency and appears to be a safe, effective and innovative technique to manage a single large HCC.